Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T20:31:53+01:00
1) 2x-1/2=3x+1 |*2
2x-1 = 6x+2
-3 = 4x | :4
x = -3/4

2)2x-1/3-x=3/5 |*(3-x)
2x-1 = 9-3x/5 |*5
10x-5 = 9-3x
13x = 14
x = 14/13

3) 2x-(3x-1)=5
2x-3x+1 = 5
-x = 4
x = -4

:)
2010-03-02T20:33:29+01:00
1) 2x-1/2=3x+1
2x-3x=1+1/2
-x=3/2
x=-3/2

2) 2x-1/3-x=3/5
2x-x=3/5+1/3
x=9/15+5/15
x=14/15

3) 2x-(3x-1)=5
2x-3x+1=5
-x=5-1
-x=4
x=-4
2010-03-02T20:33:47+01:00
1) 2x-1/2=3x+1
2x - 3x = 1 + 1/2
- x = 1,5 | :(-1 )
x = - 1,5

2) 2x-1/3-x=3/5
2x -x=3/5-1/3
x = 4/15

3)2x-(3x-1)=5
2x-3x+1=5
2x-3x=5-1
-1x=4 | : ( -1)
x = -4